Investigation of interaction between tert.-butyl diamidophosphites and alkyl halides - Salkeyeva, L.K.; Vojtíšek, P.; Minayeva, Ye.V.; Sugralina, L.M.; Omasheva, A.V.; Muratbekova, A.A.; Salkeyeva, A.K.; Sadykov, K.I. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In this article the interaction of tert.-butyldiamidophosphites with various alkyl halides with a mobile halogen atom, in particular, allyl chloride, benzyl chloride and bromomalonic ester under various conditions was studied. It was established that reactions with benzyl chloride and allyl chloride proceeded according to the classical Arbuzov reaction scheme by quartering the phosphorus atom with the formation of the corresponding benzyl and allyl amidophosphonates as the main reaction products. It was stated that the reaction proceeded ambiguously with the formation of various products mixture. This is due to the structure of the intermediate «quasiphosphonium», which depends on the nature of the solvent: the ionic form predominates in polar solvents, and the pentavalent form predominates in non-polar solvents. In addition it was proved that the direction of the reaction depended on the reaction conditions, namely, the temperature and the solvent nature. It was shown that the reaction with bromomalonic ester proceeded through the initial protonation of the phosphorus atom with the formation of a quasiphosphonium compound, the decomposition of which led to the corresponding tetraethyldiamidophosphorous acid.
Үш-бутилдиамидфосфиттердің алкилгалогенидтерімен əрекеттесуін зерттеу
Исследование взаимодействия трет-бутилдиамидофосфитов с алкилгалогенидами
Keywords: ester amides of P (III) acids; tert-butyldiamidophosphites; alkyl halides; bromomalonic ester; bromomalonic ester